2016
DOI: 10.4467/16890027ap.16.026.6095
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of the Marine Planktonic Dinoflagellate Oxytoxum and Corythodinium (Peridiniales, Dinophyceae)

Abstract: Abstract. The dinoflagellate genera Oxytoxum and Corythodinium that account for more than fifty species are widespread in warm oceans. These genera have been considered synonyms and thecal plate designations varied among authors. Several planktonic and sand-dwelling genera have been placed within the Oxytoxaceae. We obtained the first molecular data based on small subunit (SSU) rRNA gene sequences of Oxytoxum and Corythodinium, including the type species (O. scolopax and C. tessellatum) and C. frenguellii and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Both genera are morphologically similar but can be distinguish by the position of the cingulum, always anterior in Oxytoxum and median or anterior in Corythodinium, and by the larger and broader epitheca in Corythodinium (Taylor, 1976). Although some species possess intermediate characteristics between both genera; molecular data support the generic separation (Gómez et al, 2016). Within the genus Oxytoxum, Dodge and Saunders (1985) designated O. laticeps as the type species of Section Excavatum (II), which comprises species with a reduced and domed epitheca and sulcus deeply excavated and partly covered by a large list composed of extensions of Sd and 6'' plates and by a list which is an extension of 1''".…”
Section: Distribution and Habitat The Species Of The Family Oxytoxaceae Usually Occur In Low Densitiesmentioning
confidence: 78%
See 2 more Smart Citations
“…Both genera are morphologically similar but can be distinguish by the position of the cingulum, always anterior in Oxytoxum and median or anterior in Corythodinium, and by the larger and broader epitheca in Corythodinium (Taylor, 1976). Although some species possess intermediate characteristics between both genera; molecular data support the generic separation (Gómez et al, 2016). Within the genus Oxytoxum, Dodge and Saunders (1985) designated O. laticeps as the type species of Section Excavatum (II), which comprises species with a reduced and domed epitheca and sulcus deeply excavated and partly covered by a large list composed of extensions of Sd and 6'' plates and by a list which is an extension of 1''".…”
Section: Distribution and Habitat The Species Of The Family Oxytoxaceae Usually Occur In Low Densitiesmentioning
confidence: 78%
“…5C, D). It is an autotrophic species (Gómez et al, 2016). Dimensions: length average 16.7 µm ± 1.4, width average 12.4 µm ± 1.8 (n = 20).…”
Section: Oxytoxum Laticepsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this information and selected cell shape formulas from Olenina et al (2006), we calculated Vc. Only for Nézan et al (2012) and Gómez et al (2016) minimum-maximum Vc were calculated and, in these cases, mean Vc is also reported. Table S2.…”
Section: Supplementary Note 5: Estimation Of C Biomass For the Entire Phytoplankton Community (Cphyto) Based On A C:chl Seasonalitymentioning
confidence: 99%
“…A quantificação dos traços classificados nesse estudo seguiu o proposto por Moser et al (2017), sendo os registros reportados como presença ou ausência. Os traços foram determinados com o auxílio da literatura especializada contendo informações sobre características dos gêneros identificados (Guiry e Guiry, 2021; Rodríguez- Gómez et al, 2021;Sathish et al, 2021;Lavanya et al, 2020;Velázquez-Suárez et al, 2020;Díaz et al, 2019;Kaczmarska et al, 2019;Sukenik et al, 2019;Ryabushko et al, 2019;Yunes, 2019;Godrijan et al, 2018;Pacheco et al, 2016;Cros e Estrada, 2013;Nanjappa et al, 2013;Mann et al, 2017;Saldarriaga e Taylor, 2017;Eikrem et al, 2016;Gómez, et al, 2016;Dimiza et al, 2014;McCartney et al, 2014;Komárek e Johansen, 2015;Anderson et al, 2012;Harrison et al, 2011;Gómez et al, 2010;Haraguchi e Odebrecht, 2010;Al-Kandari et al, 2009;Kaczmarska et al, 2009;Gribble et al, 2009;Escalera et al, 2007;Baek et al, 2006;Tenenbaum e Gomes, 2006;Witon e Witkowski, 2006;Malinverno, 2004;Montresor et al, 2003;Hargraves, 2002;Litaker et al, 2002;Hasle, 2001;Seo e Fritz, 2001;Cox, 1999;…”
Section: Análises De Traços Funcionaisunclassified